2011
DOI: 10.1037/a0022585
|View full text |Cite
|
Sign up to set email alerts
|

Discriminant validity of the Behavior Rating Inventory of Executive Function Parent Form for children with attention-deficit/hyperactivity disorder.

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a neurodevelopmental disorder, with concomitant executive function deficits often being the focus of empirical and clinical investigation. This study explored the validity of the Behavior Rating Inventory of Executive Function Parent Form (BRIEF;Gioia, Isquith, Guy, & Kenworthy, 2000) for children with ADHD and a matched control sample. Fifty-eight children with ADHD (69% with comorbidity) and 58 matched controls were found to exhibit statistically ( p Ͻ .001)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
20
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 26 publications
4
20
0
1
Order By: Relevance
“…Since publication in 2000, the BRIEF has been widely used in school and clinical settings as well as in a wide variety of research studies involving children and adolescents who are typically developing and those with developmental disorders, medical illness, neurological disorders, and psychiatric disorders (for review, see Isquith, Roth, & Gioia, 2013;. It is one of the most sensitive measures to attention deficit/ hyperactivity disorder (ADHD; Reddy, Hale, & Brodzinsky, 2011;Toplak, Bucciarelli, Jain, & Tannock, 2008) and to changes following brain injury (Chevignard, Soo, Galvin, Catroppa, & Eren, 2012), has been widely used to assess outcome following a variety of interventions (Isquith, Roth, Kenworthy & Gioia, 2014) and is associated with academic performance (for review, see Roth et al, 2014). There are over 400 peer-reviewed publications supporting the reliability, validity, and clinical utility of the BRIEF.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Since publication in 2000, the BRIEF has been widely used in school and clinical settings as well as in a wide variety of research studies involving children and adolescents who are typically developing and those with developmental disorders, medical illness, neurological disorders, and psychiatric disorders (for review, see Isquith, Roth, & Gioia, 2013;. It is one of the most sensitive measures to attention deficit/ hyperactivity disorder (ADHD; Reddy, Hale, & Brodzinsky, 2011;Toplak, Bucciarelli, Jain, & Tannock, 2008) and to changes following brain injury (Chevignard, Soo, Galvin, Catroppa, & Eren, 2012), has been widely used to assess outcome following a variety of interventions (Isquith, Roth, Kenworthy & Gioia, 2014) and is associated with academic performance (for review, see Roth et al, 2014). There are over 400 peer-reviewed publications supporting the reliability, validity, and clinical utility of the BRIEF.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…ADHD is commonly associated with difficulties in response inhibition and poor working memory (Barkley, 2011;Schachar, 2010), both of which are components of executive functioning (EF; Reddy, Hale, & Brodzinsky, 2011). EF is a higher-order cognitive process and is composed of a multitude of complex functions that humans use on a daily basis, such as: planning, response inhibition, mental=cognitive flexibility, working memory, initiation, and set shifting (Anderson, 2002;Silver, 2014).…”
mentioning
confidence: 99%
“…A recent study revealed that parents rated a sample of children aged 6 to 16 years old with ADHD significantly higher on all subscales of the BRIEF as compared with their TD peers (Reddy et al, 2011). Research on adolescents also indicated that based on both parent and teacher ratings, adolescents with ADHD were rated significantly higher than TD peers on the Working Memory, Inhibit, Plan=Organize, and Shift subscales (Toplak et al, 2009), and ratings for the ADHD group were above the clinical cutoff, with the exception of the parent rating for the Shift subscale.…”
mentioning
confidence: 99%
“…The BRIEF was standardized and validated for use with boys and girls, and the sample used to establish normative data included a "range of racial and socioeconomic backgrounds and geographic locations, including inner city, urban, suburban, and rural environments" (Gioia et al, 2000, p. 5). Reddy, Hale, and Brodzinsky (2011) reported that the BRIEF yields "high internal consistency, with correlations ranging from .80 to .98, good test-retest reliability, and has moderate interrater reliability between parents and teacher ratings for the normative group" (p. 48). The researchers found the BRIEF to be valid in assessing school-aged children and adolescents, specifically those with ADHD, compared with a control sample.…”
Section: Adopt An Auditory-listening Test Protocolmentioning
confidence: 99%